Mobile-Based Pottery Ordering Application UI/UX Design for Banyumulek Village Handicraft Using Design Thinking Method - Taufik Muhammad; Nuraqilla Waidha Bintang Grendis; Joni Saputra (Breakthroughs In Informatics, Networking, Algorithms, Research, And Yield (BINARY), 2026)
Banyumulek Village, known as a center for traditional pottery crafts in WestNusa Tenggara, faces challenges in digital product marketing. This study aims to designa mobile-based pottery ordering application using a UI/UX approach through the DesignThinking method. The Design Thinking methodology is applied through stages includingempathize, define, ideate, prototype, and testing, involving end users directly in the designprocess. Data were collected through observations, interviews, and questionnaires withartisans and potential consumers. The result is a prototype application featuring a digitalcatalog, online payment methods, order tracking, and an intuitive and responsive user in-terface. Evaluation was conducted through usability testing and UX questionnaires, withsuccess rate reaching 97.12% based on cognitive walkthrough analysis. The Post-StudySystem Usability Questionnaire (PSSUQ) results showed SysUse score of 1.55, InfoQualof 1.43, InterQual of 1.59, and Overall of 1.58, all within the ”very good” category. Thisresearch contributes to the development of locally-based digital solutions for empoweringthe creative economy in rural communities